Groundwater and geothermal anomalies due to a prolate spheroid - HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2009)
We present an exact analytical solution  of the two potential problems which can help to understand heat  ﬂow and  groundwater ﬂow in some deep elongated geother- mal  resources.  The thermal conductivity and  diﬀusivity coeﬃcients of the spheroid  and surrounding medium  are  diﬀerent. The solutions are  expressed in terms  of the spherical functions of the ﬁrst and second kinds.  The results of numerical calculations are presented for the half-spheroidal body  at the surface of the Earth.